Research & Development (R&D) in Strategic Production of a Safest Car - Aidanazima Abashah; Shahriman A.B; Haslina Hassan Basri; Razinda Tasnim A.R; A. Harun; Z.M. Razlan; M.S.M. Hashim; W.K. Wan (International Journal of Supply Chain Management, 2019)
This study was conducted to investigate the influence of Research and Development (R&D) in producing a safer car by investigating the manufacturing safety behaviors among employees of the manufacturing company. The quantitative method of data collection was utilized to collect the data among these employees and fifty-two respondents covering different age groups, educations levels and positions in the company had answered the survey. The main statistical analysis such as Pearson Correlation and Multiple Regression was used to analyze this data gathered by using SPSS software. Based on the statistical results, the research finding displays a significant relationship between R&D and manufacturing safety behavior among automotive manufacturing employees. To conclude, R & D is one of the crucial factors for every automotive manufacturer to make sure the car produced are at the highest safety level.